Pendekatan dakwah kultural Wali Songo melalui budaya lokal dan relevansinya terhadap dakwah digital modern - Endin Amrina Fahmi; Hanun Maulidia Adzro; Nafisah Fanindra Putri; Emma Mudtiana Bahari; Aulia Paramita Bahri; Erika Diah Oktavianda; Reva Febriyanti Febriyanti; Widiya Ainur Rohima; Faricha Najwa A.; M. Erfan Muktasim B., (Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the cultural da'wah approach employed by the Wali Songo through the utilization of local culture and to examine its relevance to contemporary digital da'wah practices. The research adopts a qualitative approach using a library research design and a historical-comparative perspective. Data were collected from various scholarly sources, including academic books, journal articles, conference proceedings, theses, and other relevant scientific publications. Data analysis was conducted through content analysis to identify, interpret, and synthesize concepts related to cultural and digital da'wah. The findings reveal that the success of Wali Songo's da'wah was largely supported by persuasive, adaptive, and accommodative approaches toward local culture through the use of arts, traditions, local languages, and social institutions as mediums of religious communication. This acculturative strategy enabled the peaceful dissemination of Islamic values without generating significant social conflict. At the same time, the development of digital da'wah has introduced several challenges, including the homogenization of religious messages, the commodification of da'wah, and the transformation of religious authority under the influence of digital media algorithms. The study further demonstrates that the fundamental principles of Wali Songo's cultural da'wah remain highly relevant in the digital era, particularly in promoting contextualized religious messages, cultural sensitivity, inclusivity, and moderation. This study proposes the concept of digital-cultural da'wah, a model that integrates digital technology, Islamic values, and local cultural wisdom as an adaptive, effective, and sustainable strategy for religious communication within Indonesia's contemporary digital society.